Localization and summability of multiple Hermite series - G. E. Karadzhov; E. E. El-Adad (International Journal of Mathematics and Mathematical Sciences)
The multiple Hermite series in Rn are investigated by the Riesz summability method of order α>(n−1)/2. More precisely, localization theorems for some classes of functions are proved and sharp sufficient conditions are given. Thus the classical Szegö results are extended to the n-dimensional case. In particular, for these classes of functions the localization principle and summability on the Lebesgue set are established.